PENGARUH PROMOSI, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DAN LOYALITAS KONSUMEN PADA RENGGINNANG BERLIAN SRIANTI DI SITUBONDO - Maisaroh, Maisaroh; Hamdun, Edy Kusnadi; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal for Indonesia's economic progress, offering a robust national economic base and substantial employment opportunities. This study aims to explore how promotion, product quality, and service quality influence customer satisfaction and loyalty. Conducted as explanatory research, the study focuses on customers of Rengginang Berlian Srianti in Situbondo, sampled through simple random sampling. Data analysis and hypothesis testing utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings from Smart PLS 3.0 indicate that promotion does not significantly affect customer satisfaction, whereas product quality and service quality do. However, promotion does not significantly impact customer loyalty, nor does product quality directly influence it. Interestingly, service quality does positively affect customer loyalty. Moreover, customer satisfaction does not significantly correlate with customer Loyalty. Indirectly, Promotion positively affects Customer loyalty through customer satisfaction, albeit insignificantly. Conversely, product quality and service quality negatively influence customer loyalty via customer satisfaction, though not significantly.